P2X7 Receptor-Dependent Layer-Specific Changes in Neuron-Microglia Reactivity in the Prefrontal Cortex of a Phencyclidine Induced Mouse Model of Schizophrenia - Calovi, Stefano; Mut-Arbona, Paula; Tod, Pál; Iring, András; Nicke, Annette; Mato, Susana; Vizi, E. Sylvester; Tønnesen, Jan; Sperlagh, Beata (Frontiers in Molecular Neuroscience, 2020)
BACKGROUND: It has been consistently reported that the deficiency of the adenosine triphosphate (ATP) sensitive purinergic receptor P2X7 (P2X7R) ameliorates symptoms in animal models of brain diseases. OBJECTIVE: This study aimed to investigate the role of P2X7R in rodent models of acute and subchronic schizophrenia based on phencyclidine (PCP) delivery in animals lacking or overexpressing P2X7R, and to identify the underlying mechanisms involved. METHODS: The psychotomimetic effects of acute i.p. PCP administration in C57Bl/6J wild-type, P2X7R knockout (P2rx7-/-) and overexpressing (P2X7-EGFP) young adult mice were quantified. The medial prefrontal cortex (mPFC) of P2rx7-/- and heteroyzgous P2X7-EGFP acutely treated animals was characterized through immunohistochemical staining. The prefrontal cortices of young adult P2rx7-/- and P2rx7tg/+ mice were examined with tritiated dopamine release experiments and the functional properties of the mPFC pyramidal neurons in layer V from P2rx7-/- mice were assessed by patch-clamp recordings. P2rx7-/- animals were subjected to a 7 days subchronic systemic PCP treatment. The animals working memory performance and PFC cytokine levels were assessed. RESULTS: Our data strengthens the hypothesis that P2X7R modulates schizophrenia-like positive and cognitive symptoms in NMDA receptor antagonist models in a receptor expression level-dependent manner. P2X7R expression leads to higher medial PFC susceptibility to PCP-induced circuit hyperactivity. The mPFC of P2X7R knockout animals displayed distinct alterations in the neuronal activation pattern, microglial organization, specifically around hyperactive neurons, and were associated with lower intrinsic excitability of mPFC neurons. CONCLUSIONS: P2X7R expression exacerbated PCP-related effects in C57Bl/6J mice. Our findings suggest a pleiotropic role of P2X7R in the mPFC, consistent with the observed behavioral phenotype, regulating basal dopamine concentration, layer-specific neuronal activation, intrinsic excitability of neurons in the mPFC and the interaction of microglia with hyperactive neurons. Direct measurements of P2X7R activity in relation to microglial ramifications and dynamics could help to further elucidate the molecular mechanisms involved.